Using Wii controller in interactive digital media (Part A) - Hsieh, Pey Lun. (2009)
This Final Year Project aims to study and employ the technology behind the Wii Remote in the development of different interactive digital media applications on the PC. This report thus serves as an overview of the Wii Remote technology, as well as the theories and implementations of the various software applications developed in this project.